Des architectes urbanistes au cœur d’une lutte entre des écologies concurrentes. « Quartier libre des Lentillères » contre « écocité Jardin des maraîchers » à Dijon - Pierre Bouilhol (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
At a time when socio-environmental controversies around development projects are intensifying, new forms of activism are emerging from militant anti-capitalist occupations (“zones à défendre” or “ZAD”) in resistance to “large, ineffectual and decreed projects.” These new forms of activism and civic engagement, both local and global, have become increasingly divisive, often pitting environmentalists against one another. This essay proposes to examine the history, the narrative regimes and the unfolding consequences of a specific case of socio-environmental mobilization, the “quartier libre des Lentillères” on the outskirts of the French city of Dijon. The “quartier libre” is currently being threatened by the proposed “écocité Jardin des maraîchers,” an urban development project supported by the mayor of the city. After describing the competing viewpoints on this contested piece of land, the article focuses on the perspective of those mobilizing to oppose the development project as well as its reception by scholars and professionals working on urban questions. The form of environmental activism taking place in Dijon can be seen as a living actualization of environmental and ecological theories. While scenarios like this seem unsettling to the disciplines of architecture and urban planning, they may also represent opportunities for rethinking the role of architectural and urban interventions faced with the new realities of a heating climate.